Correction: A 3-D NanoMagnetoElectrokinetic model for ultra-high precision assembly of ferromagnetic NWs using magnetic-field assisted dielectrophoresis. Issue 69 (20th November 2020) - Singh, Sachin K.; Rajib, Md Mahadi; Drobitch, Justine L.; Atulasimha, Jayasimha; Bandyopadhyay, Supriyo; Subramanian, Arunkumar
Abstract : Correction for 'A 3-D NanoMagnetoElectrokinetic model for ultra-high precision assembly of ferromagnetic NWs using magnetic-field assisted dielectrophoresis' by Sachin K. Singh et al., RSC Adv., 2020, 10, 39763–39770, DOI: ; 10.1039/D0RA08381J .